Evaluating direct oral anticoagulants versus vitamin K antagonists for treatment of left ventricular thrombus: a systematic review and meta-analysis. (14th October 2021) - Qiu, Y; McEwen, C; Bhagirath, V; Chan, N; Eikelboom, J; Eikelboom, R; Young, J; Whitlock, R; Belley-Cote, E
Abstract: Background/Introduction: Left ventricular thrombi are associated with high rates of stroke and systemic embolism (1). While vitamin K antagonists (VKAs) have historically been the anticoagulant of choice, they have a narrow therapeutic window and require frequent monitoring. Direct oral anticoagulants (DOACs) offer more predictable anticoagulation but the use of DOACs to treat left ventricular thrombus has not been well studied (1, 2). Guideline recommendations around the topic are based on expert consensus and very low-quality evidence. Purpose: This systematic review and meta-analysis compares DOACs or VKAs in the treatment of left ventricular thrombus. Outcomes of interest were stroke and systemic embolism, thrombus resolution, any bleeding, major bleeding, and mortality. Methods: We searched CENTRAL, MEDLINE, EMBASE, CINAHL, ACPJC, and Web of Science for studies comparing DOACs and VKAs in the treatment of left ventricular thrombus. We also searched reference lists from included studies and relevant conferences' proceedings. Two reviewers independently screened titles and abstracts and then the full-text of potentially relevant citations in duplicate. They then extracted data and evaluated risk of bias in duplicate. The data was analyzed using Revman 5.3. We used the DerSimonian and Laird random-effects model to pool the weighted effect of estimates across all studies. The pooled relative risks (RRs) were calculated with corresponding 95% confidence intervals (CIs). We assessed the quality of evidence for each outcome using the Grading of Recommendations, Assessment, Development, and Evaluation approach. Results: Of 443 citations screened, 12 observational studies (n=2, 225) were included. We found no randomized controlled trial addressing the question. Most included studies were at high risk of bias due to unmatched baseline variables. We found no significant difference in any of our outcomes with DOACs versus VKAs: stroke and systemic embolism (RR 1.14, 95% CI [0.82, 1.58], p=0.43), thrombus resolution (RR 1.02, 95% CI [0.91, 1.15], p=0.69), any bleeding (RR 1.47, 95% CI [0.65, 3.33], p=0.36), major bleeding (RR 0.22, 95% CI [0.01, 4.21], p=0.32), and mortality (RR 0.99, 95% CI [0.67, 1.45], p=0.95). Evidence for each of these outcomes was of very low-quality due to risk of bias, inconsistency, and imprecision of the studies. Conclusions: Very low quality evidence suggests no difference in outcomes with DOACs versus VKAs in the treatment of left ventricular thrombus. More robust data are needed to guide clinicians. FUNDunding Acknowledgement: Type of funding sources: None.